Pengaruh Konten Tiktok @Backpackertampan terhadap Minat Traveling Generasi Milenial - Pratama, Andromeda Gilang; Nuh, Mohammad (Lembaga Yasin AlSys, 2024)
In an all-digital world like today, technological advances are becoming increasingly evident. One of them is the innovation of computerized correspondence by utilizing internet access. With the presence of the internet, social media emerged, one of its uses is to spread useful information for its users, including information about tourism destinations or traveling activities. A phenomenon that is currently booming is that you can find many TikTok accounts created to introduce a tourism place/destination, which will later display traveling content/videos. These travelers will upload or upload videos when they are visiting tourism destination areas. This study aims to determine whether there is influence and how much influence the TikTok @backpackertampan content has on the millennial generation's interest in traveling. The Uses and Effects theory is used as the main foundation in making this research. The method used in this research is a descriptive survey method using a quantitative approach. Sampling was carried out by applying a probability sampling technique of the simple random sampling type. The results of this study indicate that the @backpackertampan TikTok content has a strong positive influence on Millennial Generation Traveling Interests with a score of 0.627 which, if rounded up, becomes 63%. While the other 37% are influenced by other variables.